Habitat use by Atherinella brasiliensis (Quoy & Gaimard, 1825) in intertidal zones of a subtropical estuary, Brazil - Barbara Maichak De Carvalho (Frontiers in Marine Science, 2015)
Habitat use is different along the ontogenetic development of some species and may be influenced by environmental parameters. This study described the interaction of Atherinella brasiliensis caught in intertidal areas of the Paranaguá Estuarine Complex with environmental parameters (salinity, chlorophyll, pH and water temperature). Collections were conducted between August 2010 and July 2011, at 17 sites in the north-south axis of the Paranaguá Estuarine Complex, Brazil. CTD profiling was carried out every month to measure the environmental parameters. At each month and sampling site, a paralel trawling 30 m long was carried out using a beach seine net 5 m long, 2 m high and 2.5 mm between opposite knots. After collection, fish were identified, measured for total length, weighed and the ages were estimated according von Bertalanffy. We caught 10024 individuals with total mean length of 44.32 mm (SD ± 25.37 mm), variation range between 12 and 142 mm, and weight between 0.01 and 73 g, averaging 1.35 g (SD ± 2.66 g) and ages estimated between < 1 and 22 months. Significant differences were detected between sectors and periods for number of individuals and weight at capture, with higher mean values in the mean sector during the rainy period. The spatial and temporal distribution of ages was statistically different, individuals between < 1 and 3 months were more abundant in the sector 2 during the rainy period, and individuals older than 7 months were evenly distributed throughout the sampling area, and with higher mean abundance at the beginning and end of the dry period. Our results evidenced that all age classes of A. brasiliensis are present in shallow areas. This species shows different habitat use between age classes, which is caused by changes in feeding habits and higher availability of favorable environments, besides specific characteristics.